The relationship between nutritional status and knowledge with HB levels in adolescent girls - Chesy Sripratiwi; Erike Septa Prautami; Depita Meriyani; Jenny Ramadona Putri Ardi Yudha; Arly Febrianti (Science Midwifery, 2026)
Anemia remains a significant public health problem among Indonesian adolescent girls, as evidenced by prevalence data reaching 32% according to a national health survey. This study aims to analyze the relationship between nutritional status and knowledge with hemoglobin levels in adolescent girls at SMK NU Muara Padang. This study used a quantitative method with a cross-sectional design conducted on 52 adolescent girls selected through a purposive sampling technique. Data collection included a structured questionnaire to measure nutritional knowledge, anthropometric measurements to determine Body Mass Index, and hemoglobin level examination using a digital hemoglobinometer. Statistical analysis was performed using the Statistical Package for the Social Sciences version 26 with a chi-square test at a significance level of 0.05. The results showed that 67.3% of respondents had insufficient nutritional knowledge, data showed that 55.8% had abnormal nutritional status, and 32.7% had anemia. Chi-square analysis revealed no significant relationship between nutritional knowledge and hemoglobin levels (p = 0.51), and no significant relationship between nutritional status and hemoglobin levels (p = 0.14). Although there was no statistically significant relationship, the high prevalence of anemia and low nutritional knowledge indicate the need for comprehensive interventions. Schools and health facilities should collaborate to implement regular nutrition education programs, anemia screening, and iron supplementation to prevent and manage anemia in adolescent girls.